Three Pillars of Urbanization: Migration, Aging, and Growth - Theresa Grafeneder-Weissteiner; Klaus Prettner; Jens Südekum (De Economist, 2020)
Economic development in industrialized countries is characterized by rising per capita GDP, increasing life expectancy, and an ever greater share of the population living in cities. We explain this pattern within a regional innovation-driven economic growth model with labor mobility and a demographic structure of overlapping generations. The model shows a natural tendency for core–periphery structures to emerge in modern knowledge-based economies.
Keywords: J10; O30; O41; R23; 330; Agglomeration; Urbanization; Migration; Innovation; Growth; Core–periphery structures; Regional inequality